2022
DOI: 10.1002/pbc.29807
|View full text |Cite
|
Sign up to set email alerts
|

Successful isavuconazole salvage therapy for cerebral mucormycosis in a child with relapsed leukemia: A light in the dark tunnel

Abstract: Central nervous system mucormycosis (CNS-M) is a rare, 1 often deadly infection 2,3 with three forms: rhinocerebral mucormycosis, disseminated mucormycosis with CNS involvement, and isolated cerebral mucormycosis (ICM). 4 ICM is the rarest type 5,6 but can be rapidly progressive with high mortality (up to 65%) despite aggressive treatment. 5 We present a case of ICM in a child with relapsed leukemia where isavuconazole (ISAV) monotherapy was successfully used as salvage therapy and the patient was able to resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Once mucormycosis develops, it is often fatal due to its rapid progression [5] . Early diagnosis and treatment are therefore crucial [17] . Definitive diagnosis by invasive techniques is, however, often difficult in patients with hematologic disorders because of the high hemorrhaging tendency [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Once mucormycosis develops, it is often fatal due to its rapid progression [5] . Early diagnosis and treatment are therefore crucial [17] . Definitive diagnosis by invasive techniques is, however, often difficult in patients with hematologic disorders because of the high hemorrhaging tendency [7] .…”
Section: Discussionmentioning
confidence: 99%
“…After switching from VOR to ISA monotherapy owing to renal damage, the patient was successfully treated. Alali et al (2022) reported the case of a child with CNS-relapsed acute lymphoblastic leukemia who developed solitary cerebral IM. After debridement and L-AmB administration, the infection spread, but the infection resolved after switching to oral ISA single-agent rescue therapy.…”
Section: Immentioning
confidence: 99%
“…After switching from VOR to ISA monotherapy owing to renal damage, the patient was successfully treated. Alali et al. (2022) reported the case of a child with CNS-relapsed acute lymphoblastic leukemia who developed solitary cerebral IM.…”
Section: Clinical Efficacymentioning
confidence: 99%